GAMBARAN PEMAHAMAN GURU TENTANG EVALUASI PEMBELAJARAN DI TAMAN KANAK-KANAK SE-KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Manik, Septi Lulu; N, Zulkifli; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research focuses on understanding the kindergarten teacher education S1 on the evaluation of learning in kindergartens throughout the city districts pekanbaru a foot umbrella. The purpose of this study was to determine teachers understanding tk overview of evaluation. This research was conducted in kindergarten se umbrella of a foot-districts with the number of respondents as many as 44 teachers from 26 kindergartens there. The research is descriptive with quantitative approach with simple random sampling technique. Research results are seen learning evaluation of each indicator which is in the category of